Distinct effect of xenobiotics on the metal‐binding properties of protein molecules. (7th June 2015) - Novikova, Natalia; Kovalchuk, Mikhail; Stepina, Nina; Gaynutdinov, Radmir; Chukhrai, Elena; Yurieva, Eleonora
<x xml:space="preserve">Abstract</x> The X‐ray standing‐wave method was applied to study the elemental composition and molecular organization of ordered protein films of alkaline phosphatase exposed to different xenobiotics (drug compounds, lead). Binding of metal ions from triply distilled water to protein molecules has been experimentally observed. Definite differences in the arrangement of impurity metal ions in the films have been established. The considerable enhancement of protein–metal interactions is attributed to partial rearrangement of the protein native structure, induced by xenobiotics.